Os usos do modal Can no seriado infantil Peppa pig: uma abordagem da linguística de corpus - Martins, Daniel Fagundes [UNIFESP] (2020)
The inclusion of films and television programs in English as a Foreign Language lessons has been a common practice in the past decades, as the literature in the field attests (BEDNAREK, 2018; VEIRANO PINTO and CONDI DE SOUZA, 2011). However, to date, there are few studies that look at the language of animation for children. To fill this gap, this study aims to identify the uses of the modal can in a corpus composed of all of the episodes from seasons 1 to 5 of the British preschool animated series Peppa Pig. Corpus Linguistics provided the theoretical framework for the study. The animation series Peppa Pig was chosen because, being produced for children in the preschool age range, its dialogues simulate the language used in situations that children encounter in their daily lives. To achieve the aforementioned objective the corpus—composed of 261 transcriptions of the episodes, totaling 111,511 tokens and 5,079 types—was tagged with the semantic tagger UCREL Semantic Analysis System (USAS) and analyzed with the Lancaster University corpus toolbox (#LancsBox), both developed by Lancaster University, England. The frequency of the tags was counted with the help of the statistical software SPSS 23.0. Both USAS and SPSS were used to identify the salient semantic fields in which the modal can occurs, that is, those in which the frequency of can, can’t, and cannot is greater than 500 in at least four of the five seasons. This step was taken to contextualize the uses of the modal can semantically. The salient semantic fields identified are actions, time, movement, quantities, living creatures, relationships between family members, and physical attributes. The most frequent collocates of the 1,126 occurrences of can and can’t/cannot are the first- and second-person personal pronouns. Three general uses and 12 especific uses of can and can’t/cannot were identified. Such results confirm the hypothesis that children who watched all the episodes of the first five seasons of Peppa Pig, in English, have been exposed to many more uses of the modal can than the three uses (ability/inability, possibility, and permission) that typically figure in pedagogical materials.